2015
DOI: 10.1128/aem.00872-15
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophages Isolated from Chicken Meat and the Horizontal Transfer of Antimicrobial Resistance Genes

Abstract: c Antimicrobial resistance in microbes poses a global and increasing threat to public health. The horizontal transfer of antimicrobial resistance genes was thought to be due largely to conjugative plasmids or transposons, with only a minor part being played by transduction through bacteriophages. However, whole-genome sequencing has recently shown that the latter mechanism could be highly important in the exchange of antimicrobial resistance genes between microorganisms and environments. The transfer of antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 44 publications
(53 reference statements)
0
77
1
Order By: Relevance
“…For instance, retail chicken meat carries a number of phage capable of transferring antimicrobial resistance; of 243 phage randomly isolated from chicken meat, about 25% was able to transduce into E. coli resistance to 1 or more of the 35 antimicrobials tested (29). Based on factors like phage versus bacterial abundance, the number of phage in a transduction-competent state, and the physical conditions of various environments, Muniesa et al (8) concluded that phage-mediated horizontal transfer between intestinal bacteria or between intestinal and indigenous bacteria in extraintestinal environments was probable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, retail chicken meat carries a number of phage capable of transferring antimicrobial resistance; of 243 phage randomly isolated from chicken meat, about 25% was able to transduce into E. coli resistance to 1 or more of the 35 antimicrobials tested (29). Based on factors like phage versus bacterial abundance, the number of phage in a transduction-competent state, and the physical conditions of various environments, Muniesa et al (8) concluded that phage-mediated horizontal transfer between intestinal bacteria or between intestinal and indigenous bacteria in extraintestinal environments was probable.…”
Section: Discussionmentioning
confidence: 99%
“…(29) observed that of 243 bacteriophage randomly isolated from chicken meat, about a quarter was able to transduce resistance to one or more of the five antibiotics tested into E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…This is evident in the study of Modi et al (2013) who recently revealed that the viral metagenome (or virome) of antibiotic-treated mice was highly enriched for ARGs compared with that of non-treated control mice. However, the contribution of phages to the spread of ARGs suggests that phages may play a more significant role in the emergence and spread of ARGs than previously expected (Parsley et al 2010;Colomer-Lluch et al 2011aBalcazar 2014;Marti et al 2014b;Shousha et al 2015). These findings clearly show that phages have significant implications for the emergence and spread of antibiotic resistance.…”
Section: Phage Amr and Virulence Factors In Bacteria Sharingmentioning
confidence: 66%
“…The role of phage in transduction and horizontal transfer is assumed (Christie et al 2012). This assumption recently has been confirmed by Shousha et al (2015). They demonstrate that lysogenic phages that infect E. coli (coliphages) are able to transduce important antimicrobial resistances in chicken meat.…”
Section: Phage Amr and Virulence Factors In Bacteria Sharingmentioning
confidence: 81%
See 1 more Smart Citation